PENGEMBANGAN DAN PENGELOLAAN PANTAI MUSTIKA PANCER BERBASIS SISTEM MITIGASI BENCANA YANG BERMUATAN KEARIFAN LOKAL - Kurniadi, Herwin; Fahrurrozi, Mohammad (Nusantara Hasana Berdikari, 2022)
Mustika Pancer Beach is one of the coastal attractions in the southern part of Banyuwangi Regency which is prone to Tsunami disasters. This research was conducted to examine the coastal tourism management system and to find out the coastal tourism development system based on a disaster mitigation system containing local wisdom. The advantages of pancer beach are that it has its own uniqueness such as topography, and natural conditions that are still natural and are more in demand by local and foreign tourists who want to surf and see the size of the waves. The purpose of this research is to find out and explain about the management and development system of coastal tourism and to find out and develop the role of local wisdom in the disaster mitigation system by using secondary data analysis methods, field observations to comprehensively see the existing conditions. The analysis used is by using an internal and external potential level assessment as well as a SWOT analysis. Based on the initial results of the SWOT analysis, it can be seen from the internal strength of Mustika Pancer Beach Development and Management which is quite good and the development and management of Pancer Beach tourism has a very large opportunity. So that strategic and effective steps are needed to overcome or minimize weaknesses in the development of mustika pancer beach tourism. In terms of local wisdom, the community in general has carried out rituals regularly, but it is necessary to anticipate and master disaster mitigation and disaster response tools to minimize and avoid victims if they occur. an earthquake occurs.